(untitled) (Fiep Bulletin - online, 2014)
This research had as objective to identify how pedagogical practices of professors in physical education from Instituto Federal Catarinense (IFC) are built in classroom teaching, according to their own perceptions. Five PE professors from IFC participated in this study. It was applied a mixed questionnaire through Google Docs tools in order to collect data from those criteria: to identify which pedagogical practices have been developed by PE professors in IFC; to identify which matters and/or obstacles and positive factors in teaching are under the perspective of PE professors in IFC; to understand if PE professors are able to establish the relation between teaching and research as a procedure to knowledge production and emancipated formation. Results showed professors have been developing multiple pedagogical practices, or with focus on contextualized body movement proposals or with focus on physical fitness related to health. However, most of the professors have orientated their students during pedagogical practices by the bias of research, including the emancipatory perception of the students.